Optimizing a soil gas monitoring network layout across faults based on a seismogenic model. (May 2019) - Zhou, Huiling; Su, Hejun; Zhang, Hui; Li, Chenhua
Abstract: We undertake a sturdy body seismogenic model study along the northern margin of the West Qinling fault zone, China, to address some existing problems of neglecting scientific layout based on certain prediction theory and observation facts surrounding underground fluid monitoring networks across faults. A combination of high-density underground fluid measurements and vertical crustal deformation and seismological observations were used to elucidate the interplay between fluid dynamics, crustal deformation, and seismic activity and to comprehensively analyze the fault segment characteristics along the fault zone. We found correspondence between these parameters along the northern margin of the West Qinling fault zone. All parameters showed higher values in the Wu Shan (WS) segment than in the western Xia He–Huang Xiang Gou–Zhang Xian (XH-HXG-ZX) segment and eastern Tian Shui (TS) area. The 222 Rn concentration reached 5.0942 at BZC, and the Hg concentration reached 3.4398 at LJG in WS. Similarly, the vertical crustal deformation and seismic activity in this area were both stronger than those in the western XH–HXG–ZX and TS area. Based on the sturdy body seismogenic model, we found that the ZX and TS segments exhibited weaker activity than the surrounding areas and may be in a deep locked state under the corresponding regional stress. Compared with existing monitoring network for background value detection and comprehensive research results, we propose a technical underground flow monitoring network prototype that includes two grade I and five grade II survey sites along the northern margin of the West Qinling fault zone based on the sturdy body seismogenic model. This prototype will provide a more reliable basis for earthquake prediction, tracking and mitigation, and disaster risk reduction. The presented scheme can be used as a guideline for deploying fault soil gas monitoring networks in China. Highlights: Seismogenic model validates soil gas monitoring network layout along a fault zone. Soil gas observations effectively delineate inferred earthquake mechanisms. Soil gas monitoring network can potentially capture evolution of a fault zone.